Profil Literasi Digital pada Materi Sistem Reproduksi Kelas IX di SMP Darul Falah Cihampelas - Argarani, Dita; Fathurrohim, Muhammad Faizal (Institut Agama Islam Sunan Giri Ponorogo, 2023)
Digital literacy in the world of education is now very important because, in the 4.0 revolution era, all the information students need can be obtained in real time. This study aims to provide information about the profile of digital literacy in 9th grade students in science learning. The population in this study were grade 9 students at SMP Darul Falah Cihampelas. While the research sample is representative of classes IX E, F, G, H, and I students selected by stratified random sampling technique, The method used is descriptive-quantitative with an analysis of the percentage of questionnaire data. Based on the results of the study, it showed that the use of digital media by Darul Falah Middle School students was included in the bad category with a proportion of 30%. The realm of students' critical understanding is included in the very good category with a proportion of 83.6%. The domain of communication skills at Darul Falah Middle School is included in the very good category with a proportion of 88.6%. Thus, it is necessary to increase the use of digital media as a means for students to support the learning process at SMP Darul Falah CihampelasDigital literacy in the world of education is now very important because, in the 4.0 revolution era, all the information students need can be obtained in real time. This study aims to provide information about the profile of digital literacy in 9th grade students in science learning. The method used is descriptive-quantitative with an analysis of the percentage of questionnaire data. The population in this study were grade 9 students at SMP Darul Falah Cihampelas. While the research sample is representative of classes IX E, F, G, H, and I students selected by stratified random sampling technique. The results of the study, it showed that the use of digital media by Darul Falah Middle School students was included in the bad category with a proportion of 30%. The realm of students' critical understanding is included in the very good category with a proportion of 83.6%. The domain of communication skills at Darul Falah Middle School is included in the very good category with a proportion of 88.6%. Thus, it is necessary to increase the use of digital media as a means for students to support the learning process at SMP Darul Falah Cihampelas.